Pengaruh Efisiensi Pemberian Air dan Penambahan Bahan Organik Terhadap Pertumbuhan dan Hasil Kacang Tanah (Arachis Hypogaea L) - Satra Satra; Yosehi Mekiuw; Wahida Wahida (Musamus AE Featuring Journal, 2019)
This study aims to determine the water use efficiency (WUE) and the interaction between organic matter and the watering treatment in peanut plants. This study was held in the screen House of the agricultural Faculty of Musamus Merauke University, counted from August – November 2018. This research uses a randomized design of factorial group (RAKF) with 2 treatment factors, factor 1 watering consisting of 5 levels namely watering with the volume of water 100 ml, 200 ml, 300 ml, 400 ml, and 500 ml. As for 2nd factor, namely the addition of Organic material consisting of 4 levels, namely P0 (without organic material), PS (fertilizer charcoal husk), Pa (chicken manure fertilizer), and PSy (cow dung fertilizer), each treatment is combined and repeated 3 times. The results of this study shows that the water use efficiency has no significant effect on all research parameters and there is no interaction between the two factors for all research parameters. The best results with the highest average water use efficiency (WUE) (0.15 gr / mm) were obtained in 100 ml watering treatment with the addition of chicken manure (V1Pa).